Two millennia of North Atlantic seasonality and implications for Norse colonies - Patterson, William P. (National Academy of Sciences, 2010)
δ(18)O values of mollusks recovered from near-shore marine cores in northwest Iceland quantify significant variation in seasonal temperature over the period from ∼360 B.C. to ∼A.D. 1660. Twenty-six aragonitic bivalve specimens were selected to represent intervals of climatic interest by using core sedimentological characteristics. Carbonate powder was sequentially micromilled from shell surfaces concordant with growth banding and analyzed for stable oxygen (δ(18)O) and carbon (δ(13)C) isotope values. Because δ(18)O values record subseasonal temperature variation over the lifetime of the bivalves, these data provide the first 2,000-year secular record of North Atlantic seasonality from ca. 360 cal yr B.C. to cal yr A.D. 1660. Notable cold periods (360 B.C. to 240 B.C.; A.D. 410; and A.D. 1380 to 1420) and warm periods (230 B.C. to A.D. 140 and A.D. 640 to 760) are resolved in terms of contrast between summer and winter temperatures and seasonal temperature variability. Literature from the Viking Age (ca. 790 to 1070) during the establishment of Norse colonies (and later) in Iceland and Greenland permits comparisons between the δ(18)O temperature record and historical records, thereby demonstrating the impact of seasonal climatic extremes on the establishment, development, and, in some cases, collapse of societies in the North Atlantic.